2016
DOI: 10.1016/j.ejca.2016.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose computed tomography screening for lung cancer in populations highly exposed to tobacco: A systematic methodological appraisal of published randomised controlled trials

Abstract: Low-dose computed tomography (LDCT) screening recommendations for lung cancer are contradictory. The French National Authority for Health commissioned experts to carry a systematic review on the effectiveness, acceptability and safety of lung cancer screening with LDCT in subjects highly exposed to tobacco. We used MEDLINE and Embase databases (2003-2014) and identified 83 publications representing ten randomised control trials. Control arms and methodology varied considerably, precluding a full comparison and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…Non-calcified pulmonary nodules firstly detected during incidence screening may be entirely new (not present on a previous screen), not new (missed on a previous screen), or below the detection threshold of the respective LDCT lung cancer screening trial on the previous screen (hence, these are growing nodules). Unfortunately, lung cancer screening trials present their data concerning lung cancer rates in the various groups of non-calcified pulmonary nodules differently and the definitions of incidence nodules vary widely (4,5,10,16). The recently released British Thoracic Society Guidelines for the Investigation and Management of Pulmonary Nodules addresses this issue by stating that there is little evidence for the management of new incident nodules that appear on follow-up CTs (19).…”
Section: Review Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Non-calcified pulmonary nodules firstly detected during incidence screening may be entirely new (not present on a previous screen), not new (missed on a previous screen), or below the detection threshold of the respective LDCT lung cancer screening trial on the previous screen (hence, these are growing nodules). Unfortunately, lung cancer screening trials present their data concerning lung cancer rates in the various groups of non-calcified pulmonary nodules differently and the definitions of incidence nodules vary widely (4,5,10,16). The recently released British Thoracic Society Guidelines for the Investigation and Management of Pulmonary Nodules addresses this issue by stating that there is little evidence for the management of new incident nodules that appear on follow-up CTs (19).…”
Section: Review Articlementioning
confidence: 99%
“…Currently, lung cancer screening by LDCT is widely recommended for high-risk individuals by US guidelines (8)(9)(10)(11)(12)(13)(14)(15). However, there still is an ongoing debate if screening should be recommended for high-risk individuals in Europe, and further evidence is needed (16). Nevertheless, the vast data on (small) pulmonary nodules provided by the lung cancer screening trials enable further insights into the clinical management of pulmonary nodules and the development of…”
Section: Introductionmentioning
confidence: 99%
“…The majority of these guidelines recommend low-dose chest CT lung cancer screening, but under strictly controlled conditions. In France, in 2014, a task force commissioned by the French National Authority for Health (HAS) conducted a review of the literature on the efficacy, acceptability and safety of low-dose chest CT lung cancer screening and concluded that the level of proof was insufficient to recommend a national lung cancer screening programme, as the benefit-risk balance was unknown 13. The most recent review of the literature on lung cancer screening, published in 2016, reached a similar conclusion that the benefit-risk balance of low-dose chest CT screening has not been correctly documented 14.…”
Section: Introductionmentioning
confidence: 99%
“…Following the conclusions of the working group, a recent review of the literature on the effectiveness, acceptability and safety of lung cancer screening with LDCT in subjects highly exposed to tobacco determined, in regard to the lack of strong scientific evidence, that LDCT screening should not be recommended in subjects with high exposures to tobacco [ 39 ].…”
Section: Discussionmentioning
confidence: 99%